Implementation of AES-192 cryptography and QR code to verify the authenticity of budi luhur university student certificate - Pramusinto, Wahyu; Trya Sartana, Bruri; Mulyati, Sri; Amini, Safrina (Universitas Negeri Padang, 2020)
Nowadays a letter can easily be falsified and used for things that are not appropriate. Budi Luhur University has a work unit that serves student requests for certificate of active students and certificate of graduation. Students need that certificate for apply a job or get a scholarship. To prevent the falsification of letters, a system using PHP programming language and MariaDB database was used to verify the letters. The certificate released by this system will be equipped with a QR Code containing the URL with parameters that have been encrypted with the cryptographic method AES-192. If accessed, this URL will display the data number, name, letter number and date of the letter. The recipient letter can verify the authenticity of the letter by comparing the data in the letter with the data in the system. If the two data are the same, the letter is the original. Based on test results, this system can be used to guarantee the authenticity of a letter.